Analisa Komposisi Material Barium M-Heksaferit (BAM) Berbahan Dasar Pasir Besi Pantai Cilacap dan Taluk Kuantan - Dianita Wardani; Dewi Kurniasih; Aditya Maharani; Ratna Budiawati (Journal of Applied Electrical Engineering, 2022)
Analyzing the material composition of iron sand from Cilacap beach and iron sand from Taluk Kuantan beach in Riau. In this research, the synthesis of barium M-Hexaferrite is made from iron sand from Cilacap beach and iron sand from Taluk Kuantan beach, Riau. In the research method, the test was carried out using composition analysis with FTIR test. The characteristics of the test using the FTIR test that the iron sand of the Cilacap beach has an Fe content of 86.53% and does not carry out refining. while the iron sand of Taluk Kuantan beach has an Fe content of 82.86% and is not purified. Based on the wave number value, BAM doped with Cu has the best wave number value and the highest transmittance value is around 92% at wavelengths from 1467.03 to 669.56 cm−1.